IMPLEMENTASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 30/PUU-XVI/2018 TERKAIT PELARANGAN JABATAN FUNGSIONARIS PARTAI POLITIK DALAM PENCALONAN ANGGOTA DPD - Bima Krisna Bayu; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2021)
One of the problems in Indonesian constitutionality is the issue of implementation, several questions arose when the Constitutional Court decision Number 30 / PUU-XVI / 2018 was issued. In this decision, the Constitutional Court expanded the phrase